Momentum Space Properties of Atoms and Molecules - Dutta, Mala (Asian Journal of Chemistry, 2010)
The determination of structure and properties of biomolecularsystems have opened new concepts in chemistry by obtainingaccurate electron charge densities. For a long time, the densityfunctional theory has played a major role in predicting the electronicstructures of the above systems. In the light of this, the AnalyticalModel Density (AMD) function proposed by L.F. Parios has beenused to calculate the momentum space properties for representativeelements and their combination in molecular form. The results arein good agreement with Hartree-Fock estimates. Further, the cuspcondition ‹ Δ2ρ › / ‹ρr-1 › has been calculated which is vital in assigningthe accurate description of electron density at the nucleus.